Assessment of risk factors and MACE rate among occluded and non-occluded NSTEMI patients undergoing coronary artery angiography: A retrospective cross-sectional study in Multan, Pakistan - Ahmad, Ibtasam; Haris, Muhammad; Javed, Amnah; Azhar, Muhammad (Journal of Cardiology and Cardiovascular Medicine, 2018)
Objectives: The prime focus of the present study was to evaluate the most occluded coronary artery (OCA) among non-ST elevated myocardial infarction (NSTEMI) patients, and risk factors associated with occluded and non-occluded NSTEMI. Also, major adverse cardiovascular event (MACE) were evaluated among patients during index hospitalization. Methods: A retrospective, cross-sectional study was conducted in Multan Institute of Cardiology, Pakistan between 1st February, 2017, and 31st September, 2017. The data were collected from medical records of the outpatients and inpatients who were index hospitalized. Data were analyzed by using Statistical Packages for Social Sciences (IBM SPSS Statistics for Windows, Version 21.0. Armonk, NY: IBM Corp.) And Microsoft Excel (MS Office 2010). Results: Among 624 patients, angiographic findings revealed that 63.9% were suffering from non-occlusive NSTEMI while 36.1% of the patients had occluded NSTEMI. In occluded NSTEMI patients, 30.3% were having single vessel occlusion while 5.8% were having multi-vessel occlusion. Also, 49.8% were having occlusion of right coronary artery (CA) while 44% were having occluded left anterior descending (LAD) artery. Multivariate analysis revealed that age (p=0.001) and left ventricular ejection fraction (LVEF) (p=0.001) had a statistically significant association. The incidence of MACE was high among non-OCA patients as compared to OCA patients but no statistically significant association was found (p=0.44). Conclusions: Angiography confirmed that most of the NSTEMI patients had OCA. But the MACE rate was not significantly differ among OCA and non-OCA patients. The risk factors associated with OCA were low LVEF and age.